2021
DOI: 10.1186/s40729-021-00350-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital planning in zygomatic implants

Abstract: Background Zygomatic implants have been described as a therapeutic alternative for patients with severe maxillary atrophy in order to avoid bone augmentation procedures. Taking that into account, in these treatments, the key factor is the position of the implant, the virtual surgical planning (VSP) is widespread among most clinicians before surgery on the patient. However, there are no studies which evaluate the clinical relevance of these VSP. The aim of this study is to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…After removing duplicates ( n = 56), 51 articles were screened using title-abstract-keyword reading, leaving 35 reports eligible (substantial agreement, κ = 0.95). After full-text reading and a subsequent search for relevant citations, 14 studies were included in this systematic review [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 19 , 32 , 33 , 34 , 35 , 36 , 37 ] (100% of agreement among the reviewers) ( Figure 1 ). One current retrospective study from Wu included [ 19 ], and other fives studies from the same team (Shanghai Jiaotong University) were excluded due to the same population were collected in Wu’s publication [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplicates ( n = 56), 51 articles were screened using title-abstract-keyword reading, leaving 35 reports eligible (substantial agreement, κ = 0.95). After full-text reading and a subsequent search for relevant citations, 14 studies were included in this systematic review [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 19 , 32 , 33 , 34 , 35 , 36 , 37 ] (100% of agreement among the reviewers) ( Figure 1 ). One current retrospective study from Wu included [ 19 ], and other fives studies from the same team (Shanghai Jiaotong University) were excluded due to the same population were collected in Wu’s publication [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristics of the included studies are described in Table 1 according to guidance approach, system, number of examinations, ZI characteristics, and conclusions. A total of 14 studies [ 8 , 10 , 11 , 12 , 13 , 14 , 15 , 19 , 32 , 33 , 34 , 35 , 36 , 37 ], including one RCT [ 32 ], two retrospective studies [ 15 , 19 ], five prospective studies [ 12 , 13 , 33 , 34 , 37 ], six cadaver studies with one comparative analysis [ 8 , 10 , 11 , 14 , 35 , 36 ], were retrieved from the search. Those reported ZI planned/placed accuracy in 144 patients (77 male and 67 female) and 35 cadavers with total of 511 ZIs (Nobel Biocare: 274, Southern Implant: 42, SIN Implant: 16, non-mentioned: 179); six studies used 35 cadavers with 118 ZIs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schiroli et al and Vosselman et al also designed and fabricated surgical template specific for ZI surgery and gained high accuracy in ZI placement (Schiroli et al, 2016 ; Vosselman et al, 2021 ). Seldom study reported the accuracy in freehand ZI surgery, Gao et al applied digital ZI planning but conducted ZI surgery by freehand, the entry, exit, and angle deviations of 14 ZIs were 4.99 ± 2.66 mm, 6.11 ± 4.28 mm and 8.36 ± 5.3 degrees, respectively (Xing Gao et al, 2021 ). Compared with freehand surgery, the accuracy was improved in static guided ZI surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In 2000, Schramm and co‐workers 3 reported, for the first time, the use of navigational surgery for the reconstruction of postoperative defects of the maxilla with ZIs, showing that the procedure can be precisely performed with the help of preoperative planning. Other studies have demonstrated the accuracy of digital planning in the use of ZIs in an atrophic but intact maxilla to avoid bone reconstruction procedures as well as in the reconstruction of mid‐facial defects 4–8 . However, to the best of our knowledge, there are no previous studies on the use or virtual planning for ZI placement in maxillary defects by integrating prosthetic rehabilitation‐driven techniques.…”
Section: Introductionmentioning
confidence: 99%